1991
DOI: 10.1038/351164a0
|View full text |Cite
|
Sign up to set email alerts
|

Key residues involved in calcium-binding motifs in EGF-like domains

Abstract: Many extracellular proteins with diverse functions contain domains similar to epidermal growth factor (EGF), a number of which have a consensus Asp/Asn, Asp/Asn, Asp*/Asn*, Tyr/Phe (where the asterisk denotes a beta-hydroxylated residue). These include the coagulation factors IX and X, proteins with two EGF-like domains, the first of which contains the consensus residues. The first EGF-like domain of human factor IX contains a calcium-binding site, which is believed to be responsible for one of the high-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
171
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(177 citation statements)
references
References 19 publications
5
171
0
1
Order By: Relevance
“…Five EGF-like domains are present (Appella et al, 1988;Campbell and Bork, 1993): three are found in tandem (aa 147±189, 190±236 and 237±290) whereas two other domains present in a less conserved form are also identified in the same region, overlapping with the others (aa 118±159 and 263±343). None of these domains contains the laminintype or calcium-binding EGF-like domain signature (Engel, 1989;Handford et al, 1991). In addition, a stretch of amino acids located at position 83±129 obeys the chitin binding consensus described for (b1-4)-N-acetyl-D-glucosamine polymer specific lectins and plant chitinases (Wright et al, 1991).…”
Section: Molecular Characterization Of the Cdna And Of The Gene Encodmentioning
confidence: 99%
“…Five EGF-like domains are present (Appella et al, 1988;Campbell and Bork, 1993): three are found in tandem (aa 147±189, 190±236 and 237±290) whereas two other domains present in a less conserved form are also identified in the same region, overlapping with the others (aa 118±159 and 263±343). None of these domains contains the laminintype or calcium-binding EGF-like domain signature (Engel, 1989;Handford et al, 1991). In addition, a stretch of amino acids located at position 83±129 obeys the chitin binding consensus described for (b1-4)-N-acetyl-D-glucosamine polymer specific lectins and plant chitinases (Wright et al, 1991).…”
Section: Molecular Characterization Of the Cdna And Of The Gene Encodmentioning
confidence: 99%
“…, is present at the head of some EGF-like structures. The nel protein has the consensus sequence of the type I1 Ca2+ binding site (Handford et al, 1991) at the head of the second and fifth EGF-like structures. The presumed cytoplasmic domain of the nel protein is a cysteine rich structure similar to the C-terminal structure of the adhesion factor von Willebrand factor and does not have the functionally catalytic sequence such as that of kinases.…”
Section: Fig 5 Southern Blot Hybridization Analysis Of Animal Dnas mentioning
confidence: 99%
“…A subset of these domains contains a calcium binding (cb) consensus sequence, i.e. (D/N)X(D/N)(E/Q)X m (D/ N)*X n (Y/F) (where m and n are variable, and * indicates a potential ␀-hydroxylation site) (3)(4)(5) (Fig. 1a).…”
mentioning
confidence: 99%